Pendampingan Mediasi Kasus Tindak Pidana Penganiayaan di Bangkalan - Anam, Afdolul; Rozi, Fahrur (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2023)
criminal law, the resolution of criminal acts is through nonlitigation channels with the terms penal mediation and restorative justice. Penal mediation is a process to reconcile the disputing parties. Mediation is an alternative method and way of resolving a dispute in which the disputing parties submit the resolution to the mediator with the aim of obtaining a fair result that is acceptable to the disputing parties. In this case, the mediator explains the role of mediating between the disputing parties. This role is realized through the mediator's task of actively assisting the parties in providing a correct understanding of the dispute they are facing and providing the best alternative solution for resolving the dispute proposed by the mediator. Meanwhile, restorative justice is an approach that focuses more on the direct participation of perpetrators, victims and the community in the process of resolving criminal cases. This community service in assisting the mediation process for criminal acts of abuse aims to provide the best solution for the parties involved so that it does not lead to further legal proceedings.